2013
DOI: 10.1002/pmic.201300204
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the bovine uterine proteome is associated with stage of cycle and concentration of systemic progesterone

Abstract: Early embryonic loss accounts for over 70% of total embryonic and foetal loss in dairy cattle. Early embryonic development and survival is associated with the concentration of systemic progesterone. To determine if the uterine proteome is influenced by stage of cycle or systemic progesterone concentrations, uterine flushings were collected from the ipsi- and contralateral uterine horns of beef heifers on Days 7 (n = 10) and 15 (n = 10) of the oestrous cycle. Animals were separated into low or high progesterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 117 publications
(137 reference statements)
0
43
0
Order By: Relevance
“…The stimulatory effect of P4 on trophoblast elongation, although indirect via the endometrium, is unequivocal. This effect is a result of downstream effects of P4-induced changes in gene expression in cells of the endometrium (Satterfield et al 2006, 2012b resulting in changes in the composition of ULF to which the developing embryo is exposed (Faulkner et al 2013) (Fig. 1).…”
Section: Conceptus Size and Progesterone Studiesmentioning
confidence: 99%
“…The stimulatory effect of P4 on trophoblast elongation, although indirect via the endometrium, is unequivocal. This effect is a result of downstream effects of P4-induced changes in gene expression in cells of the endometrium (Satterfield et al 2006, 2012b resulting in changes in the composition of ULF to which the developing embryo is exposed (Faulkner et al 2013) (Fig. 1).…”
Section: Conceptus Size and Progesterone Studiesmentioning
confidence: 99%
“…To maintain the uterine functions, different proteins secreted by the endometrium act on sperm viability (Martus, Verhage, Mavrogianis, & Thibodeaux, ), embryo metabolism, implantation and maintenance of the corpus luteum (Ziecik et al, ). For this reason, the study of such proteins at specific times (different stages of the oestrous cycle or during pregnancy) has relevance in the reproduction of females, given that their quantity and type change according to the physiological status (Faulkner, Elia, & O'Boyle, P., Dunn, M., & Morris, D., ) and may interfere in the periovulatory phase, which is the period normally used for the transfer of embryos in cloning biotechniques (Martins et al , ). In recent years, studies have used methods in proteomics to investigate the uterine molecular dynamics as related to uterus physiology in the caprine species (Koch et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that protein synthesis remains under the control of steroid hormones and alterations in protein profiles during pregnancy can be related to the changes in gestational hormonal profile. Faulkner et al confirmed this relationship in cyclic cows and Balestrieri et al in pregnant cows.…”
Section: Introductionmentioning
confidence: 74%